Building the Causal Attribution Scale of Winning and Losing for Basketball Coaches - Hawraa Mohammed Ali Hassan; Aya Muayad Sadoon (Institute of Medico-legal Publications Pvt Ltd, 2021)
Sports psychology is concerned with studying human behavior as a living being that seeks to adapt to thestimulation and the sports coach is one of the samples to which this applies, as he has to follow a certainbehavior to deal with his players, which requires him to form his own philosophy and this philosophyappears clearly through his training profession As the work in training aims to gain more respect and selfesteem and good social status.All of this appears through the sporting competition that ends either with winning or losing, and here comesto the coach’s mind the evaluation of many justifications and the reasons behind the gain or loss, includingpersonal and external or administrative reasons, and here the issue of causal attribution emerges, and thereis no study that has identified this topic and for this This study aimed to build a measure of the causalattribution of victory and loss for basketball coaches.